Thermodynamic modeling of the Bi-M (M = Ti, Cr, V) systems - Cao Z.; Xin J.; Chen C.; Liu S.; Hu B.; Tang C.; Du Y. (Journal of Mining and Metallurgy. Section B: Metallurgy, 2013)
The Bi-M (M = Ti, Cr, V) systems have been critically reviewed and modeled by means of the CALPHAD technique. All the intermetallics (BiTi3, BiTi2, Bi9Ti8, Bi3Ti2 and Bi2Ti) were treated as stoichiometric compounds. The enthalpy of formation at 0 K for BiTi2 was computed via first-principles calculations to assist the thermodynamic modeling. The gas phases for the Bi-Cr and Bi-V systems were treated as ideal gas. A set of self-consistent thermodynamic parameters has been finally obtained for each of these binary systems. Comparisons between the calculated and measured phase diagrams as well as first-principles calculations show that most of experimental data can be satisfactorily reproduced by the present thermodynamic descriptions.